Provisions of the Arbitration Clause in the Marine Bill of Lading (Comparative Study) - Moayad Abdulmunam, Assist. Lect. Areej (Basra studies journal, 2023)
The international commercial arbitration system has become one of the most important systems in resolving disputes in various fields, including the maritime field. However, the multiplicity of parties to the maritime relationship and then the multiplicity of issued documents may raise some problems for us, including those related to identifying the parties to one document and then protesting against this document. Which may include the arbitration clause, in addition to that, the arbitration clause may not be included directly in a specific document, but may be referred to by virtue of a clause included in one of the documents, and this method also raises a problem for us about the validity of this referral and what are its conditions and requirements, this is despite the multiplicity of documents It may lead to a conflict of provisions and procedures included in each of them; Accordingly, and in the light of these dilemmas, we divided the subject of this research into two sections, one to discuss the definition of the marine bill of lading and determine its relationship to the charter party of the ship, and the other to discuss the controls of the arbitration clause in the marine bill of lading, which includes images of the arbitration clause and its effects in the marine bill of lading. To a set of results, the most important of which are: The marine bill of lading is an independent document from the ship charter party. However, this independence does not mean a complete severance of the relationship between them as long as the two documents have one goal, which is to facilitate the maritime operation. This is what justifies the transfer of the arbitration clause to a non-contractual one through merger or assignment, and also it became clear to us that it requires the acceptance of the marine bill of lading holder for the validity of the arbitration clause (listed or merged) in his confrontation, and this acceptance is required in order for it to be valid to be an acceptance independent of the acceptance The maritime bill of lading based on the principle of the independence of the arbitration agreement from the original contract, and it also became clear to us that it is required for the validity of the merger or assignment as well as the acceptance condition that the assignment be written and specified on the condition of arbitration and not a general assignment. An Iraqi who is in agreement with modern maritime legislation and international maritime agreements, and the need for this law to include a legal article specific to the merged arbitration clause, such as the following: - (If one of the maritime documents included a provision for referring the dispute to arbitration and the bill of lading was issued without including a clear and special reference to this text and did not The knowledge and acceptance of the bearer of the bill of lading is achieved for this provision, so it is not permissible at that time to invoke it against the bearer of the bill of good faith).